2013
DOI: 10.1088/0004-637x/779/2/157
|View full text |Cite
|
Sign up to set email alerts
|

Twist Accumulation and Topology Structure of a Solar Magnetic Flux Rope

Abstract: To study the build up of a magnetic flux rope before a major flare and coronal mass ejection (CME), we compute the magnetic helicity injection, twist accumulation, and the topology structure of the three dimensional magnetic field, which is derived by the nonlinear force-free field model. The Extreme-ultraviolet Imaging Telescope on board the Solar and Heliospheric Observatory observed a series of confined flares without any CME before a major flare with a CME at 23:02 UT on 2005 January 15 in active region NO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
104
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(114 citation statements)
references
References 99 publications
(124 reference statements)
9
104
0
1
Order By: Relevance
“…DEM analysis shows that the MFR top and footpoints were heated to over 6.0 MK. It is hypothesized that the heating may result from the reconnection near the periphery of the MFR, i.e., QSLs, where the magnetic linkages undergo drastic changes and, hence, strong current layers are formed there (Demoulin et al 1996;Savcheva et al 2012b;Guo et al 2013). The reconnection in the presumed QSLs has two important roles in the slow rise phase.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…DEM analysis shows that the MFR top and footpoints were heated to over 6.0 MK. It is hypothesized that the heating may result from the reconnection near the periphery of the MFR, i.e., QSLs, where the magnetic linkages undergo drastic changes and, hence, strong current layers are formed there (Demoulin et al 1996;Savcheva et al 2012b;Guo et al 2013). The reconnection in the presumed QSLs has two important roles in the slow rise phase.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…1, which is calculated by sampling points on the z-axis. These Φ num values are calculated by the integration of the angular variation along the magnetic axis curve of MFR (Guo et al 2013). Its value on the MFR surface is about five turns, which means the MFR is kink unstable.…”
Section: Numerical Simulation Set-upmentioning
confidence: 99%
“…Preprocessing the magnetogram has been very popular Schrijver et al 2008;De Rosa et al 2009;Tadesse et al 2009;Guo et al 2013;Cheng et al 2014;Jiang et al 2014;Wang et al 2015), which makes it more consistent with NLFFF. Metcalf et al (2008) showed that preprocessing improved the metrics quantifying the agreement between the NLFFF solution and reference model field.…”
Section: Preprocessmentioning
confidence: 99%